Growth and yield comparison of rice treated with Trichoderma asperellum (UPM 40) in flooded and saturated soil condition - Yusup, Iffatul Arifah (2021)
Malaysian consumed 2.7 million MT rice per year. Only 67% of the amount is produced locally and the rest of the number is imported from Thailand, Vietnam, Pakistan and other countries. Most of the crops are planted in conventional flooded rice cultivation which requires proper water irrigation in order to make sure enough water supplied to the field. Limitation of water will suppress plant growth which reduce plant height, flowering and retarded maturity and at the end causes less yield production. Trichoderma can beneficially interact with plant roots and can induce disease resistance, plant growth promotion and tolerance to abiotic stresses including drought. Thus, this study is aimed to determine the optimum rate of encapsulated T. asperellum (UPM 40) in improving rice growth and yield, to study growth and yield performance of rice plants through the application of encapsulated T. asperellum (UPM 40) in saturated and flooded soil conditions and to evaluate the effects of encapsulated T. asperellum (UPM 40) on rice plants in response to drought stress. The study was consists of two separated experiment. The first study was carried out by planting rice plants in different soil conditions while treated with different rates of T. asperellum (UPM40). Rates of encapsulated T. asperellum (UPM 40) were 0, 1, 3 and 5 g. The soil conditions were consist of saturated and flooded water level. From the results 5 g encapsulated T. asperelllum (UPM 40) was the best rate as 1000 grains weights, harvest index, total yield, spikelet weight per panicle, percentage of filled grains per panicle, number of filled grains per panilce, relative chlorophyll content, maximum root area, root volume and root length of the rice plants were significantly better than the other treatments. The best rate of the experiment (5 g) was carried to the second experiment which was aimed to evaluate effect of encapsulated T. asperellum (UPM 40) on rice plants during drought stress at early anthesis. The outcome was the encapsulated T. asperellum (UPM 40) had significantly improve growth and yield of the rice plants under drought stress. Relative water content of rice plants treated with T. asperellum (UPM 40) was 78.51%, higher than control with 72.09% has shown the ability of the fungus to help rice plants alleviate detrimental effects of drought stress. The application helped to delay the onset of adverse effects of drought stress to the crop simultaneously improving rice yield as compared to untreated plants. Thus, encapsulated T. asperellum (UPM 40) may help farmers to reduce yield loss during drought season.